Issues related to sustainable tsetse and trypanosomosis management strategies and rural Development - Politzar, H.; Omamo, Steven Were; D'Ieteren, G.D.M. (OAU/STRC, 2001)
This paper explores the elements of a sound policy toward tsetse and trypanosomosis control by highlighting key issues in policy design and implementation. A framework is proposed that suggests that consistent policy toward tsetse and trypanosomosis control hinges on strong links with broad rural Development objectives and strategies, and in particular on the potential for increasing agricultural productivity via control. A broad review of recent trends in tsetse and trypanosomosis control in Africa is presented. The policy framework is then detailed and illustrated by examples from a number of African countries. Conclusions are drawn regarding policy coherence and transparency and implications for policy research.